Ultrasound colonography in visualization of large intestine cancer pathology - N. V. Tumanskaya; A. A. Fedusenko (Zaporožskij Medicinskij Žurnal)
Introduction: colon oncopathology takes the 2-nd place among different kinds of cancer and tends to grow constantly. Thus, the incidence of colorectal cancer (CRC) in Ukraine is 20.6 cases per 100 thousands of population. 70-75% of patients are diagnosed only at the 3-4 stage of the disease, due to its long asymptomatic initial period.